Where the sidewalk ends : the poems & drawings of Shel Silverstein. - Silverstein, Shel (HarperCollins, 2004)
A boy who turns into a TV set and a girl who eats a whale are only two of the characters in a collection of humorous poetry illustrated with the author's own drawings.